Transport(s) in the British Empire and the Commonwealth - Lurdos, Michèle; Misrahi-Barak, Judith (Horizons anglophones, 2007)
'Transport' is a delightfully open word; adding an 's' to the original makes it even more interesting. The participants in the Conference which was organized on this topic by the Cerpac, early November 2005 at the Université Paul-Valéry, Montpellier (France), explored several facets of the word. They started with 'Means of transport', in Australia, New Zealand and South Africa. They then moved to 'Forced transport', which dealt with West African slaves, Tasmanian Aborigines, Indo-Caribbean women and Japanese-Canadians. 'Travel' offered some gentler kind of transport, from India to South Carolina and the Tongan Islands. And the very same word offered a way of 'Crossing Borders' with the symbolism in Salman Rushdie's or V.S. Naipaul's novels, or the transfer of mentalities in the 18th century. All in all, we covered a lot of ground from beginning to end. And now, readers, just allow yourselves to be. . . transported.